AB1191 Within-patient analysis during anakinra and canakinumab treatment in cryopyrin associated periodic syndrome. (23rd January 2014) - Caorsi, R.; Lepore, L.; Zulian, F.; Alessio, M.; Stabile, A.; Finetti, M.; Bibalo, C.; Martini, A.; Gattorno, M.
Abstract : Background: Anti-IL1 drugs have been shown to be an effective treatment for the control of disease activity in patients with CAPS. Anakinra has been used for several years and his long-term efficacy and safety has been demonstrated; Canakinumab has been recently described as an effective treatment in CAPS, even if by this time few follow-up data are available. Objectives: To compare the efficacy and the impact on the quality of life in CAPS patients receiving the two IL1-blockers during their disease course. Methods: 11 patients (F:M =6:5, 8 children and 3 adults) with a clinical diagnosis of CINCA (7 pts), Muckle-Wells syndrome (MWS, 2 pts), MWS overlapping CINCA (2 pts) were analyzed. All patients, who received a previous treatment with Anakinra, were enrolled in the CACZ885D2306 trial(1) and then treated in compassionate use for the following 12 months. Disease activity, laboratory parameters, doses of IL-1 inhibitors and health related quality of life were analyzed at the time of the last administration of Anakinra and after 12 months of compassionate use with Canakinumab. Health related quality of life was assessed with the Child Health Questionnaire (CHQ-PF 50). Results: At the last administration of Anakinra the patients were treated with a mean dose of 1, 38 mg/kg/day (range 0, 66-2). Six patients (3 CINCA, 1 MWS/CINCA and 2 MWS) displayed a complete response while a partial response was observed in 5 patients (4 CINCA, 1 MWS/CINCA patients), due to a slight increase of acute phase reactants. At the last follow-up during Canakinumab treatment 4 patients (2 MWS, 1 MWS/CINCA and 1 CINCA patients) were treated with a stable dose of 2 mg/kg (or 150 mg if weight was higher than 40 kg) every 8 weeks, all of them displaying a complete response. Two CINCA patients were treated with the dose of 2 mg/kg (or 150 mg) every 7 and 6 weeks respectively, with a complete response. Four patients (3 CINCA and 1 MWS/CINCA patients) were treated with the dosage of 300 mg with a frequency of 7, 6, 5 and 4 weeks. All of them displayed a partial response. One CINCA patient discontinued the treatment due to persistent relapse and poor compliance. The evaluation of the quality of life with the CHQ-PF50 questionnaire did not reveal a significant difference of the impact of the two drugs on physical concepts (Phs 51.88 during Anakinra, 51.55 during Canakinumab), while Canakinumab determined a significant amelioration of psychosocial concepts (PsS 47.03 during Anakinra, 54.01 during Canakinumab; p<0.03, Wilcoxon Pairs Test), especially of the parental perception of the disease (p<0.05). Conclusions: This study shows that both Anakinra and Canakinumab are able to completely control the clinical manifestations associated to CAPS. In general Anakinra was able to better control the elevation of acute phase reactants. In the other hand, while both drugs were able to normalize many aspect of health related quality of life, Canakinumab showed a better impact on the psychosocial concepts. References: Two-year results from an open-label, multicentre, phase III study evaluating the safety and efficacy of canakinumab in patients with cryopyrin-associated periodic syndrome across different severity phenotypes. Kummerle-Dechner et al, ARD 2011. Disclosure of Interest: R. Caorsi: None Declared, L. Lepore: None Declared, F. Zulian: None Declared, M. Alessio: None Declared, A. Stabile: None Declared, M. Finetti: None Declared, C. Bibalo: None Declared, A. Martini: None Declared, M. Gattorno Grant/Research support from: Novartis, Consultant for: Novarits, Speakers Bureau: Sobi